Do prisoners trust the healthcare system? - Lindsey A. Vandergrift; Paul P. Christopher (BMC, 2021)
Abstract Background Individuals who are incarcerated have greater healthcare needs than non-justice-involved individuals, yet incarcerated individuals often report substandard care. There are disproportionate numbers of black, indigenous, and people of color (BIPOC) in prison, who, even in general society face greater obstacles to accessing healthcare and have worse health outcomes due to structural racism. Regardless of race, people with criminal justice involvement often report stigma from the non-carceral healthcare system. Providing sufficient healthcare in carceral settings themselves is complicated by lack of privacy and the inherent dialectic of prisons that restrict freedom and providers focusing on healing and health. Based on these adverse experiences, people who are incarcerated may have decreased distrust in the healthcare system, deterring individuals from getting adequate medical care. Methods In this exploratory study, health care system distrust was evaluated among 200 people who were incarcerated using the Revised Health Care System Distrust scale, a community-validated, 9-item measure comprised of 2 subscales (values and competence distrust). Results Distrust was moderately and positively associated with participant age (r s  = 0.150, p = 0.034), with the second-oldest quintile (33 to 42-year-olds) reporting the highest level of overall and competence distrust. Participants identifying as Non-Latinx White reported higher competence distrust compared to Latinx and Non-Latinx/Non-White respondents. Conclusions These preliminary findings suggest that select groups of prisoners may be less likely to trust the healthcare system, highlighting an impediment to receiving adequate care while incarcerated. Further study of this topic is warranted.